Synthesis of polysubstituted quinolines through promoter-regulated selective annulation and C–C bond cleavage from 2-styrylanilines and β-keto esters. Issue 21 (8th July 2020) - Xu, Hui; Yu, Fei; Huang, Ronglu; Weng, Mingyue; Chen, Hong; Zhang, Ze
Abstract : I2 and Mn(OAc)3 regulated annulation of 2-styrylanilines and β-keto esters is accomplished for chemoselective synthesis of 2-alkylquinolines and quinoline-2-carboxylates. Abstract : A powerful construction of 2-alkylquinolines and quinoline-2-carboxylates has been successfully accomplished employing I2 and Mn(OAc)3, respectively, to promote the annulation of 2-styrylanilines and β-keto esters accompanied by selective C–C bond cleavage. Following this promoter-regulated strategy, various 2-alkylquinolines and quinoline-2-carboxylates were chemoselectively synthesized from easily available 2-styrylanilines and β-keto esters. The reaction mechanism is also tentatively investigated.